Development of novel nanomaterials based electrocatalysts for energy conversion devices - Sekar, Archana (Kansas State University, 2023)
The growing global energy demand, due to the depletion of fossil fuels and accompanied global warming, has compelled the utilization of renewable and sustainable energy sources. This has attracted the investigation of electrochemical renewable energy conversion devices, such as fuel cells and water electrolyzers which can provide higher energy conversion efficiency at lower temperature with negligible environmental pollution. Fuel cells produce electricity from renewable chemicals (liquid methanol, hydrogen, air etc.), while water electrolyzers produce renewable chemicals (hydrogen and oxygen) utilizing electricity and water. The electrocatalysts used in fuel cell and water electrolzyers are key to enhance their performances. Despite the advances in both the technologies, they are not commercially successful yet owing to high cost and poor durability of Pt based electrocatalysts used to catalyze the electrochemical reactions. This dissertation focusses on the development of novel electrocatalysts, and catalyst supports for fuel cells and water electrolyzers using microwave-assisted synthesis methods. In the first approach, a simple microwave assisted synthesis methods has been developed to prepare multifunctional core-shell catalyst supports and PtRu nanoparticles to employ as methanol oxidation reaction (MOR) anode electrocatalysts in direct methanol fuel cells (DMFC). The specific heating of microwaves has been used to selectively deposit ultra-thin shell of metal oxides (such as TiO₂ and SnO₂) on carbon supports and PtRu nanoparticles on TiO₂/C or SnO₂/C supports. Thermal annealing of these electrocatalysts has resulted in formation of PtRu alloy nanoparticles and defective metal oxide ultra-thin shells. Systematic materials and half-cell electrochemical characterizations has been done in Chapter 2 to show the improved carbon monoxide (CO) oxidation kinetics, superior MOR activity, and excellent stability exhibited by the PtRu alloy nanoparticles deposited on TiO₂ or SnO₂ modified carbon supports, when compared to commercial PtRu/C catalysts. The enhanced MOR activity and stability is attributed to the strong-metal support interaction (SMSI) and higher oxophilicity offered by the ultra-thin metal oxide shell on PtRu nanoparticles. The effect of different carbon supports and different metal oxides in the activity and stability of PtRu electrocatalysts have been studied in Chapters 3 and 4, respectively, with full DMFC evaluations. The excellent properties imparted by the ultra-thin shells of TiO₂ modified carbon supports have been found to enhance the hydrogen oxidation reaction (HOR) anode kinetics of PtRu electrocatalysts in anion exchange membrane fuel cells (AEMFCs) in Chapter 5. About 20% enhancement in maximum power density in AEMFC has been achieved compared to the commercial PtRu/C anode. In the second approach, one-dimensional chain like structures of amorphous molybdenum trisulfide (MoS₃) has been deposited on reduced graphene oxides (rGO), using a rapid microwave assisted synthesis method, to employ as a platinum group metal free hydrogen evolution reaction (HER) electrocatalyst to use in proton-exchange membrane water electrolzyers (PEMWEs). A family of MoS[subscript x]/rGO hybrid materials with controllable composition and structure, has been produced by subjecting the microwave prepared samples to thermal annealing at different temperatures in reducing atmosphere. The amorphous MoS₃/rGO annealed at 250 degrees Celsius (a-MoS₃/rGO 250) exhibits excellent HER catalytic activity with a low overpotential, a low Tafel slope, a high double layer capacitance and a high turnover frequency value. The enhanced catalytic activity of a-MoS₃/rGO 250 has been attributed to the high density of Mo[superscript V] active sites and the abundant sulfur ligands of the a-MoS₃/rGO 250. Overall, microwave assisted synthesis method has been found to be a versatile and a rapid platform to prepare high performance electrocatalysts for fuel cells and water electrolyzers.
Keywords: Renewable energy; Direct methanol fuel cell; Hydrogen evolution reaction; Methanol oxidation reaction; Carbon nanotubes; Platinum group metals